2007
DOI: 10.1126/science.1145626
|View full text |Cite
|
Sign up to set email alerts
|

Production of Trout Offspring from Triploid Salmon Parents

Abstract: Many salmonids have become at risk of extinction. For teleosts whose eggs cannot be cryopreserved, developing techniques other than egg cryopreservation to save genetic resources is imperative. In this study, spermatogonia from rainbow trout were intraperitoneally transplanted into newly hatched sterile triploid masu salmon. Transplanted trout spermatogonia underwent spermatogenesis and oogenesis in male and female recipients, respectively. At 2 years after transplantation, triploid salmon recipients only prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
168
2
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(185 citation statements)
references
References 4 publications
3
168
2
12
Order By: Relevance
“…Gonia within a testis (spermatogonia) or an ovary (oogonia) contain germ stem cells capable of self-renewal and differentiation even in culture (Hong et al, 2004). Transplantation data in fish support that gonia are sexually indeterminate or plastic (Okutsu et al, 2006;Okutsu et al, 2007;Yoshizaki et al, 2010). However, there is no evidence for the absence or presence of gonial sex (Kocer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Gonia within a testis (spermatogonia) or an ovary (oogonia) contain germ stem cells capable of self-renewal and differentiation even in culture (Hong et al, 2004). Transplantation data in fish support that gonia are sexually indeterminate or plastic (Okutsu et al, 2006;Okutsu et al, 2007;Yoshizaki et al, 2010). However, there is no evidence for the absence or presence of gonial sex (Kocer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This approach represents a significant development for germline transmission of cultured cells, and will be a potential reproduction technology to combat infertility in vertebrates including human. Additionally, primordial germ cells (PGCs) and spermatogonial stem cells could be transplanted between two different salmonid species, and resulted in production of donor-derived offspring [45][46][47]. In combination with natural and artificial polyploid fishes with special reproduction modes [18,48], the surrogate approach might have significant values for producing polyploidy stocks in aquaculture or for restoring an endangered species in wild life conservation.…”
Section: Somatic Cell Nuclear Transfer and Stem Cell Technologies In mentioning
confidence: 99%
“…Saito et al (2011) have shown that a single PGCs transplantation technique works even between marine and freshwater species. Okutsu et al (2007) have also produced germline chimeras by transplanting rainbow trout (Oncorhynchus mykiss) spermatogonia from adult testis into sterile hatched larvae of masu salmon (O. masou), and they clearly showed that the germline chimeras generated only gametes of the donor. On the other hand, a transplantation technique has been developed both in tilapia and atherinopsid species, respectively, where spermatogonia from a donor were inserted directly into an adult recipient testis via genital pore (Majhi et al 2009;Lacerda et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is difficult to prepare PGCs in the amount appropriate for transplantation. Regarding the spermatogonia transplantation by Okutsu et al (2007), Majhi et al (2009) or Lacerda et al (2010, although numerous cells can be prepared from an adult fish, the efficiency of germline chimerism is low.…”
Section: Introductionmentioning
confidence: 99%